Digital Transformation and Audit Innovation in Waqf Institutions: A Systematic Literature Review - Saputra, Wali (Indo Publishing, 2025)
This study aims to systematically review and synthesize the literature on the relationship between digital transformation and audit innovation within waqf institutions. The focus is on how technological advancements influence transparency, accountability, and governance in Islamic social finance. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). A total of 72 academic articles published between 2010 and 2025 were analyzed, sourced from reputable databases such as Scopus, Web of Science, ScienceDirect, Taylor & Francis, and Emerald Insight. The analysis employed bibliometric mapping using VOSviewer and thematic analysis to identify research trends, major themes, and the conceptual framework surrounding digital audit transformation in waqf institutions. The results reveal that digital transformation in waqf governance has progressed through three main phases: Digital recordkeeping (2010–2015), Fintech integration (2016–2020), and Adoption of blockchain-based and AI-powered audit systems (2021–2025). Four dominant research themes emerged: Digital infrastructure integration, Blockchain-enabled transparency, AI-driven audit analytics, Shariah-compliant audit governance frameworks. From these findings, the study proposes a conceptual model: Digital Transformation → Audit Innovation → Improved Governance → Waqf Sustainability. Digital audit innovation enhances efficiency, transparency, and public trust in waqf financial reporting, while also reducing the risk of mismanagement and moral hazard. However, challenges remain in the form of limited digital literacy, a lack of standardized technology-based Shariah audit regulations, and infrastructure disparities across waqf institutions. As a result, national bodies such as the Indonesian Waqf Board (BWI) are encouraged to develop standardized digital Shariah audit frameworks and capacity-building programs for waqf managers (nazhir) and Islamic auditors. This study contributes to the advancement of Islamic digital auditing by integrating technological dimensions with maqashid al-shariah–based ethical considerations. The resulting conceptual model offers a balanced digital governance structure that aligns technological efficiency with Islamic moral and spiritual accountability.